Human health risk assessment of heavy metals in street foods from selected area in Kota Bharu, Kelantan - Mohamed, Nurul Ain (Universiti Sains Malaysia, 2016)
The progress of industries has led to the increased of pollutants emission into the environments. One of the most common pollutants is heavy metals. Excess consumption of metals elements can cause chronic disease for consumers in the future. The common heavy metals that are often found in the food samples are plumbum (Pb), manganese (Mn) and copper (Cu). Therefore, the study was conducted to assess the level of heavy metals of Pb, Mn and Cu concentration in street foods sold at selected area in Kota Bharu, Kelantan. This study also deals with human health risk assessment of metal contamination through the consumption of street foods. The level of heavy metals in streets foods was compared to the level of heavy metal in non-street foods that sampled from Health Campus Universiti Sains Malaysia’s cafeterias. The food samples were digested prior being analyzed using atomic absorption spectrometry (AAS) method. The results showed that concentration of Pb, Mn and Cu decreased in the following sequenced: Pb > Mn > Cu. The mean of Pb concentration is higher than Mn and Cu in street foods. The average concentration of Pb, Mn and Cu were approximately 0.665mg/kg, 0.188mg/kg and 0.021mg/kg. Besides, the level of heavy metal Pb and Cu was higher in street foods compared to non-street foods and the result was different from concentration of Mn which is lower. Target Hazard Quotient (THQ) was used in the health risk assessment to determine carcinogenicity of the food samples. The result shows that the concentration and THQ of all metal studied (Pb, Mn, Cu) are less than 1; signified that a daily exposure at this level is unlikely to cause any adverse effects during a person lifetime. In conclusion, there is a heavy metal presence in street foods, but the THQ value showed the foods is not dangerous to be consumed.